PENGARUH PENGGUNAAN STRATEGI CONTEXTUAL TEACHING LEARNING DALAM MENINGKATKAN KETERAMPILAN PENGGUNAAN UANG KERTAS PADA ANAK TUNA GRAHITA RINGAN DI SLB ASIH MANUNGGAL - Lia Dyani, - (2021)
Contextual Teaching and Learning (CTL) is the linkage of each material or learning topic with real life. Based on the results of interviews and observations that have been conducted by researchers at SLB Asih Manunggal, the problems found are that there are some child students with intellectual barriers who still experience obstacles in using money skills. The research method used is an experimental method with single subject research (SSR) with A-B-A design. with the habit of learning to find something to solve problems in their life through practice and it is hoped that through this direct practice children can understand and improve skills in using money. The effect of the Contextual Learning strategy on money-using skills can be proven by looking at the average level obtained during the research phase, namely 40.9 for the mean baseline level-1 (A1), 66.1 for the intervention phase (B) and 82.03. for the mean level at baseline-2 phase. Then in the overlapping data analysis, the baseline-1 (A1) phase to the intervention phase (B) had a low proportion, which was 0% as well as the intervention phase (B) to the baseline-2 phase. Keywords: Contextual Learning Strategies, Skills to Use Money,